1996
DOI: 10.1007/bf03402203
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis for Recessive Dystrophic Epidermolysis Bullosa in 10 Families by Mutation and Haplotype Analysis in the Type VII Collagen Gene (COL7A1)

Abstract: Background: Epidermolysis bullosa (EB) is a group of heritable diseases that manifest as blistering and erosions of the skin and mucous membranes. In the dystrophic forms of EB (DEB), the diagnostic hallmark is abnormalities in the anchoring fibrils, attachment structures beneath the cutaneous basement membrane zone. The major component of anchoring fibrils is type VII collagen, and DEB has been linked to the type VII collagen gene (COL7A1) at 3p21, with no evidence for locus heterogeneity. Due to life-threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 29 publications
1
34
0
2
Order By: Relevance
“…In the British population, three recurrent PTC-causing mutations have been described: R578X, 7786delG and R2814X. 25 26 32-34 R578X and R2814X were also seen in our study, mainly in patients of European ancestry, although one Hispanic patient exhibited the R2814X mutation. Three mutations, 5818delC, 6573+1 GRC and E2857X, have been detected only in Japanese patients with RDEB; all were seen in our patients as well, with 5818delC and 6573+1 GRC detected in Japanese patients and E2857X found in one Korean family.…”
Section: Recurrent Mutations In Col7a1supporting
confidence: 64%
See 1 more Smart Citation
“…In the British population, three recurrent PTC-causing mutations have been described: R578X, 7786delG and R2814X. 25 26 32-34 R578X and R2814X were also seen in our study, mainly in patients of European ancestry, although one Hispanic patient exhibited the R2814X mutation. Three mutations, 5818delC, 6573+1 GRC and E2857X, have been detected only in Japanese patients with RDEB; all were seen in our patients as well, with 5818delC and 6573+1 GRC detected in Japanese patients and E2857X found in one Korean family.…”
Section: Recurrent Mutations In Col7a1supporting
confidence: 64%
“…[23][24][25][26][27][28] Four of these mutations were previously undescribed, whereas the rest have been reported in the literature. These recurrent mutations in our cohort were not restricted to any particular ethnic background, although the mutation 425ARG was seen mainly in patients of European ancestry.…”
Section: Recurrent Mutations In Col7a1mentioning
confidence: 99%
“…In order to establish the cause of the recurrence of c.6527dupC and c.7708delG we performed haplotype analysis for 16 and 11 carrier families, respectively. One intragenic single nucleotide polymorphism (c.2820G/A) and three informative microsatellite markers (D3S1581, D3S1289 and D3S1029) in linkage with the COL7A1 locus were studied [7,8]. Results showed that c.6527dupC segregated with a single haplotype, demonstrating a common ancestral origin.…”
mentioning
confidence: 97%
“…The following intragenic polymorphic sites of COL7A1 were analyzed: the AluI site in exon 14, the PvuII site in exon 21, and the MspI site in exon 30 [Christiano et al, 1994b]. Genotyping for the D3S1235, D3S1573, D3S1581, and D3S1076 microsatellites markers linked to COL7A1 was performed by fluorescent PCR analysis in the automatic sequencer, using the primers and the amplification conditions reported by Christiano et al [1996c].…”
Section: Haplotype Analysismentioning
confidence: 99%